THE PROCESS OF INCREASING THE FIRE RESISTANCE OF KNIVES FOR CUTTING FOOD MATERIALS (Conferencea, 2023)
Information about raising productivity of work of cutting machines and stability of cutting tools in the result of proper organization of the process of macro-and microgeometric sharpening parameters of the edge of the cutting tools is given in the article.